Quality of life in women with breast cancer - Barnaś, Edyta; Skręt, Andrzej; Skręt-Magierło, Joanna; Sobolewski, Marek (Menopause Review/Przegląd Menopauzalny, 2009)
Introduction: Breast cancer is one of the most frequent malignancies in Polish women. Survival increases due to early diagnosis and effective treatment. As a result, it becomes a chronic disease with consequences concerning bio-psycho-social functioning and changes in quality of life. Objective: The purpose of this study was to evaluate quality of life in women with breast cancer. Material and methods: The following questionnaires were used to evaluate quality of life: the EORTC QLQ-C30 and the QLQ BR-32 module. The study group comprised of 65 women, members of the Post-Mastectomy Women’s Club “Amazons” in Rzeszow. The study took place in 2007. Results: Mean time since surgery was 4.9 years. The analysis of scores obtained in various functioning subscales of the QLQ-C30 questionnaire showed no differences. The best results were noted in physical functioning and social roles. The least frequent complaints given by the respondents included nausea, vomiting, diarrhoea, and decreased appetite. Insomnia, financial difficulties, and fatigue were the most frequent ones. As far as the scales evaluating quality of life related to cancer was concerned, the highest scores were noted when asking about the body image while sexual pleasure got the lowest score. Complaints related to breast cancer concerned mainly the breast where the tumour was located and/ or its area. It was shown that the longer period of time passed since surgery the more intense adverse symptoms in the hand on the operated side were observed. Conclusions: The results of this study indicate the necessity of wide spectrum of psychophysical rehabilitation of women after breast cancer therapy irrespective of how long ago the diagnosis and treatment took place. These interventions should be realized by people trained how to educate and support cancer patients.